Survey data of perception and evaluation of umami taste in AustriaZenodo - Emilia Iannilli; Emilise Lucerne Pötz (Data in Brief, 2025)
The data presented in this work was collected in Austria. We aimed to investigate the familiarity and perception of people in this region with the umami taste. Umami, one of the five primary tastes, plays a crucial role in reducing salt intake and influencing food preferences, as demonstrated by several studies. However, despite its presence in both natural and prepared foods, Europeans appear to be largely unfamiliar with this taste compared to people in Asia.The main focus of our survey was the perception and hedonic evaluation of umami using an open-answer format. To achieve this, we collected a wide range of categorical descriptors related to the umami taste and its pleasantness compared to a simple cooking salt (NaCl) solution. We used unlabeled dark glass mist spray bottles to present the solutions on the tongues of the participants and asked for their descriptions. Additionally, we gathered information on taste preferences for the five basic tastes, preferences for spicy food, eating habits such as the addition of salt to meals, sweets consumed, travel habits, the size of participants' residential cities, and demographic information, resulting in a total of 38 variables.Our sample consisted of 309 adult participants, with a mean age of 26.7 years, recruited from public centers in Graz and the surrounding areas. This dataset has practical implications and can be valuable for sensory scientists and consumer behavior researchers seeking better to understand umami perception and acceptance in Western culture.